1991
DOI: 10.1021/bi00224a003
|View full text |Cite
|
Sign up to set email alerts
|

.alpha.-Bungarotoxin and the competing antibody WF6 interact with different amino acids within the same cholinergic subsite

Abstract: In the nicotinic acetylcholine receptors (AChRs), the sequence segment surrounding two invariant vicinal cysteinyl residues at positions 192 and 193 of the alpha subunit contains important structural component(s) of the binding site for acetylcholine and high molecular weight cholinergic antagonists, like snake alpha-neurotoxins. At least a second sequence region contributes to the formation of the cholinergic site. Studying the binding of alpha-bungarotoxin and three different monoclonal antibodies, able to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 70 publications
7
39
1
Order By: Relevance
“…That the fragment Ta185-199 1s implicated m binding of long-chain curaremlmetlc toxins 1s m agreement with the literature [20,21,23,24,26,27,34,36] We now show that a short-chain toxin also recognizes this region but with lower affinity This finding contrasts with data from Ruan et al [33] who reported that 'region a182-198 was not a bmdmg region for short-neurotoxins' However, these authors used a different bmdmg protocol and the peptlde used m their study had no dlsulfide, a factor that may greatly influence the toxin bmdmg…”
Section: Tounssupporting
confidence: 84%
See 1 more Smart Citation
“…That the fragment Ta185-199 1s implicated m binding of long-chain curaremlmetlc toxins 1s m agreement with the literature [20,21,23,24,26,27,34,36] We now show that a short-chain toxin also recognizes this region but with lower affinity This finding contrasts with data from Ruan et al [33] who reported that 'region a182-198 was not a bmdmg region for short-neurotoxins' However, these authors used a different bmdmg protocol and the peptlde used m their study had no dlsulfide, a factor that may greatly influence the toxin bmdmg…”
Section: Tounssupporting
confidence: 84%
“…More precise defimtion of the curaremimetic toxin bmdmg site has been attempted wtth fragments of a subunits generated as proteolytic [15-l 81, synthetic [19][20][21][22][23][24][25][26][27] or fusion peptides obtained by genetic means It is accepted that the region around the cysteme 192-193 is recognized by most AcChoR hgands. Systematic replacement of the residues by alanme suggest a special contribution of residues Tyr-190, Cys-192, Cys-193, Val-188, Thr-189, to formatton of toxin-peptide complexes [31].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) ␣-BTX bound to h␣-(1-210) with a high affinity (K d ϭ 5.1 Ϯ 2.4 nM). High affinity binding of ␣-BTX to the AChR ␣ subunit is routinely used to indicate correct folding of the recombinant molecule as the formation of the binding site requires the coordination of several post-translational events that draw together different regions of the ␣ subunit (11,12). (iv) The small competitive antagonists, dtubocurarine and gallamine, inhibited ␣-BTX binding to h␣- .…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that the binding sites for both acetylcholine and ␣-BTX are located close to two adjacent cysteine residues at positions 192 and 193 of the ␣ subunit (10). Moreover, other distinct regions on either the ␣ subunit (11,12) or the adjacent ␥ or ␦ subunits (13) have been shown to contribute to ␣-BTX binding, whereas the role of glycosylation at residue ␣141 (14 -16) requires further study.…”
mentioning
confidence: 99%
“…Initial screening of hybridoma cells was by ELISA [15], emplclying fusion protein I1 (0.05 pg/well of the microtiter plate)…”
Section: Production Of Monoclonal Antibodies; Immunization and Screenmentioning
confidence: 99%